Centered Structures and Trend Changes in Academic Narratives of 10-year Development of Hierarchical Medical System in China - ZHANG Shue, WANG Yanping, WANG Hongni, ZHAO Xin, CHENG Siyu, JI Keyu, WANG Xiaohe, ZHANG Meng, SUN Tao (Zhongguo quanke yixue, 2022)
BackgroundThe narratives of hierarchical medical sytem are generally classified into two patterns, one is the policy narrative, which is used to persuade the target audience to gain their support in practice, and the other is the academic narrative, which describes the thinking process of researchers to explore problems and enhance perceptions using words. The narratives of the hierarchical medical system are rich and diverse, but have been rarely systematically reviewed and summarized.ObjectiveWe explored the evolution process, focuses and characteristics of academic narratives of 10-year development of hierarchical medical system in China using social network analysis, aiming to provide a reference for improving the implementation of hierarchical medical system.MethodsOn March 21, 2021, we searched the database of CNKI for studies regarding hierarchical medical system in China published in academic journals in Chinese during January 1, 2009 to March 21, 2021 using "hierarchical medical system" "seeking healthcare in an orderly way" "seeking diagnosis and treatment services in an orderly way" "division of healthcare" "division of diagnosis and treatment" "first contact in primary care" "treating acute and chronic diseases separately" "cooperation between tertiary and secondary/primary hospitals" "bi-directional referrals" as keywords. Bibliometric methods, SATI 3.0 and UCINET 6.0 were used to explore the process, focuses and characteristics of academic narratives of hierarchical medical system through time series analysis, high-frequency keywords analysis, centrality analysis and small group analysis, and to generate visualized co-occurrence network diagrams of high-frequency keywords.ResultsA total of 4 882 studies were included for analysis. According to the results of time series analysis, the development of the hierarchical medical system could be roughly divided into three stages: embryonic stage (2009—2013) , acceleration stage (2014—2017) and standardization stage (2018 to present) . In terms of the use of frequency, the top five high-frequency keywords were "hierarchical medical system" "medical consortium" "primary healthcare institutions" "bi-directional referrals" and "public hospitals". In terms of closeness centrality, the top five high-frequency keywords were "hierarchical medical system" "medical consortium" "primary healthcare institutions" "bi-directional referrals" and "general practitioners". Small-group analysis yielded three groups of word clusters: core word clusters (including "medical consortium" "reform of public hospitals" "bi-directional referrals" "general practitioners" and "first contact in primary care") , secondary word clusters (including "the internet" "internet-based healthcare" "internet-based hospital" and "telemedicine") , and marginal word clusters (including "diabetes" "chronic disease" "cognition" and "influencing factors") . Health policy rhetoric was an important part of the core word clusters. And secondary and marginal word clusters were constantly evolving and generating.ConclusionThe academic narratives of hierarchical medical system have gradually derived from the mutually-promoted development of policies and real implementation regarding the hierarchical medical system, generally demonstrated various structures and relatively homogeneous research direction. Available academic and policy narratives of the hierarchical medical system are still limited to the scope of guiding principles, and the implementation of the concept and system still relies on the top-down push from the policy-making level, while the self-motivated micro-practices of hierarchical medical system in primary care have not yet emerged.